1881 Ind. Rev. Stat. 372 - (:unkn) unknown (My University, 1881)
§§ 1986-1987: Prohibited selling, bartering, exchanging, disposing of, or furnishing any dirk, Bowie-knife, slung-shot, metal knuckles, pistol cartridges, or other deadly weapon which can be carried concealed, to anyone under the age of twenty-one.
Keywords: TRANSFER - MINORS